2018
DOI: 10.1080/17429145.2018.1441451
|View full text |Cite
|
Sign up to set email alerts
|

Macrophomina phaseolinaalters the biochemical pathway inVigna radiatachastened by Zn2+and FYM to improve plant growth

Abstract: Mung bean [Vigna radiata (L.) Wilczek] is an important cash pulse crop extensively cultivated in the arid region of Pakistan, which encounters intimidating charcoal rot disease caused by Macrophomina phaseolina (Tassi) Goid. The current research was conducted to check the potential of Zn (1.25, 2.44 and 5 mg kg −1) and FYM [farmyard manure (1% and 2%)] in mono-, bi-and trilateral interaction in managing disease and improving yield. Suppression of plant immunity by M. phaseolina was indicated by the change in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…The net outcome of Zn fertilization, therefore, might result in a faster and stronger induction of basal defense mechanisms through genetic or biochemical modifications in tomato plant upon exposure to A. solani . Likewise, Khan et al (2018) suggested that Zn (2.5 and 5.0 mg/kg) fertilization significantly reduced charcoal rot disease and improved biological attributes in mung bean through altering physiological and biochemical attributes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The net outcome of Zn fertilization, therefore, might result in a faster and stronger induction of basal defense mechanisms through genetic or biochemical modifications in tomato plant upon exposure to A. solani . Likewise, Khan et al (2018) suggested that Zn (2.5 and 5.0 mg/kg) fertilization significantly reduced charcoal rot disease and improved biological attributes in mung bean through altering physiological and biochemical attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Basal application of Zn (2.5 & 5.0 mg/kg) alone and in combination with other nutrients (NPK, Mg & B) exhibited the excellent impact on the reduction of EB disease intensity, along with improvement in health and stress markers, however, 5.0 mg/kg Zn dose showed more promising results. Zn as a micronutrient helps to induce resistance in the plant against A. solani because it is a critical nutrient for several vital biological functions in plants like photosynthesis, growth regulation, sugar formation, seed production and defense mechanisms ( Khan et al, 2018 ). Zn may induce its toxic effect on A. solani through effecting its metabolism and enzymatic activity as reported earlier on other microorganisms by Zn nanoparticles ( Chai et al, 2015 ; Shen et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations